2013
DOI: 10.1186/1745-6673-8-7
|View full text |Cite
|
Sign up to set email alerts
|

Fatal snake bites – sociodemography, latency pattern of injuries

Abstract: BackgroundIndia is a thickly populated country; apart from having biodiversity among people, climate does change from place to place. Western Ghats of South India harbors variety of plantations and diverse creatures. Agriculture is the primary occupation of the people and some tribes living in these regions. Here majority are callous/ ignorant in employing neither advanced farming techniques nor safety precautions, hence are exposed to bites and stings by animals. Of these, snake bites cause significant mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…With poor access to health facilities, they often resort to traditional faith healers, who indulge in practices such as chanting, incisions, attempts to suck venom from the bite site, tying tourniquets, or local application of herbs, cow dung, or snakestones. 10 13 30 These measures can delay treatment 20 31 and result in increased mortality. 13 25…”
Section: High Mortality From Snakebitesmentioning
confidence: 99%
See 1 more Smart Citation
“…With poor access to health facilities, they often resort to traditional faith healers, who indulge in practices such as chanting, incisions, attempts to suck venom from the bite site, tying tourniquets, or local application of herbs, cow dung, or snakestones. 10 13 30 These measures can delay treatment 20 31 and result in increased mortality. 13 25…”
Section: High Mortality From Snakebitesmentioning
confidence: 99%
“…Snakebites are more common among the poor. 8 20 Poor housing conditions and inadequate lighting provide easy access to snakes into living spaces and they are not easily spotted. 18 Open houses, sleeping on the floor, and open defecation are other factors increasing the risk of snake encounters 8 …”
mentioning
confidence: 99%
“…Most of the bites happened during the rainy season from May to October, when most villagers are working in the fields for rice cultivation. The age, sex and seasonal distribution are similar in other regions of the world [ 13 , 26 , 27 ]. In Phin district the seasonal difference is less distinct with a considerable number of snakebites during the dry season, most likely because many villagers in this area are working in the forest during that time with a high risk of snakebite.…”
Section: Discussionmentioning
confidence: 61%
“…He acquired data on human development index (HDI), per capita expenditure on health, the percentage labour force in agriculture and gross domestic product (GDP) from databases on 138 countries for which snakebite-induced mortality rates have been estimated and each analysis illustrated a strong association between snakebite-induced mortality and poverty [ 25 ]. Rao et al found that approximately 87% of snakebite victims with fatal outcome in Southern India lived below poverty line [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most snakebite victims are men and people aged 15–54 years which is related to the fact that men spend more time in nature and outdoors ( 14 , 15 ). Studies also show that most of the bite sites are on lower limbs and the least bite sites are related to head and neck ( 16 , 17 ). The average incidence of snakebite in Iran was estimated to be 6.9 per 100000 and Ardabil province, with incidence of 4.1 per 100000, is the country’s 19th rank of snakebite incidence ( 1 , 2 ) and according to hospital evidence, snakebite in Ardabil province is relatively high.…”
Section: Introductionmentioning
confidence: 99%